2021
DOI: 10.1007/s11356-021-15832-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental pollution on the physical health of middle-aged and older adults in China

Abstract: While several studies have demonstrated the negative impacts of environmental pollution on population health, in general, few studies have examined the potential differential effects on the health of middleaged and older populations, i.e. 45 years and older. Given the twin concerns of environmental pollution and population aging in China, this article employed a xed effects model to infer the impact of environmental pollution on public health with a particular focus on middle-aged and older adults. The analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…However, no significant associations were found between sex and GDP. Previous studies have found that older adults are more susceptible to the impacts of air pollution (Fan et al, 2022;Gaines et al, 2023;Gu et al, 2020;Kan et al, 2008), which may be a result of the vulnerability of respiratory function in the elderly. For stratified analysis by season, our study found that patients were more affected by pollutants except O 3 , PM 2.5 , and PM 10 during cold seasons.…”
Section: Discussionmentioning
confidence: 98%
“…However, no significant associations were found between sex and GDP. Previous studies have found that older adults are more susceptible to the impacts of air pollution (Fan et al, 2022;Gaines et al, 2023;Gu et al, 2020;Kan et al, 2008), which may be a result of the vulnerability of respiratory function in the elderly. For stratified analysis by season, our study found that patients were more affected by pollutants except O 3 , PM 2.5 , and PM 10 during cold seasons.…”
Section: Discussionmentioning
confidence: 98%
“…Outdoor air pollution can spread from the home to urban areas, eventually becoming a global problem. Outdoor air pollution is the world's second most important air pollution problem, behind indoor air pollution, according to the Blacksmith Institute's World's Worst Polluted Places report from 2008 [12]. Pollution in the air can occur everywhere.…”
Section: Discussionmentioning
confidence: 99%
“…Lead, copper, zinc, iron chromium, and silica are all found in volcanic ash [11]. CO2 is one of the main causes of air pollution caused by volcanic eruptions, among the numerous gases generated by volcanic eruptions [12]. All volcanoes in the world are estimated to emit 0.13 -0.44 billion tons of CO2/per year [13].…”
Section: Introductionmentioning
confidence: 99%
“…The aging speed in China has exceeded that in most developed countries 29 . As population aging continues, DAPP is likely to subsequently increase 30 .…”
Section: Population Aging Is the Most Important Challenge In Controll...mentioning
confidence: 99%